2020
DOI: 10.1021/acs.inorgchem.0c02098
|View full text |Cite
|
Sign up to set email alerts
|

Mn2+ Complexes Containing Sulfonamide Groups with pH-Responsive Relaxivity

Abstract: We present two ligands containing a N-ethyl-4-(trifluoromethyl)­benzenesulfonamide group attached to either a 6,6′-(azanediylbis­(methylene))­dipicolinic acid unit (H3DPASAm) or a 2,2′-(1,4,7-triazonane-1,4-diyl)­diacetic acid macrocyclic platform (H3NO2ASAm). These ligands were designed to provide a pH-dependent relaxivity response upon complexation with Mn2+ in aqueous solution. The protonation constants of the ligands and the stability constants of the Mn2+ complexes were determined using potentiometric tit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 82 publications
1
24
0
Order By: Relevance
“…The synthesis of the ligand H 3 NO2ASAm was reported in a previous work. 40 Ligand H 2 NO2AM was prepared by alkylation of commercially available NO2A(O t Bu) 2 with 2-chloroacetamide by using acetonitrile as a solvent and K 2 CO 3 as a base. Subsequent hydrolysis of the tert -butyl esters under acidic conditions provided the ligand as the trifluoroacetate salt with 91% overall yield.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The synthesis of the ligand H 3 NO2ASAm was reported in a previous work. 40 Ligand H 2 NO2AM was prepared by alkylation of commercially available NO2A(O t Bu) 2 with 2-chloroacetamide by using acetonitrile as a solvent and K 2 CO 3 as a base. Subsequent hydrolysis of the tert -butyl esters under acidic conditions provided the ligand as the trifluoroacetate salt with 91% overall yield.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of the ligand H 3 NO2ASAm was reported in a previous work . Ligand H 2 NO2AM was prepared by alkylation of commercially available NO2A­(O t Bu) 2 with 2-chloroacetamide by using acetonitrile as a solvent and K 2 CO 3 as a base.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This proton binding process of sulfonamide group is reversible. 92 Some metal ion-sensitive MRI studies have also been reported. Sherry's group prepared a Mn(II)-based zinc-sensitive MRI CA (41, Fig.…”
Section: Manganese Complexes As Stimuli-responsive Mri Agentsmentioning
confidence: 99%
“…Fruit juices that are rich in manganese ions fulfill most of the above requirements, and therefore they are conveniently used in magnetic resonance cholangiopancreatography 3–7 . Similar to gadolinium(III), whose complexes with multidentate ligands are used as intravenous MRI contrast agents, manganese(II) is a paramagnetic ion that can increase the longitudinal relaxation rate ( R 1 ) of the neighboring water protons, thus increasing their signal intensity in T1‐weighted MRI images 3,8–10 . This causes a higher contrast between tissues where the paramagnetic ions are absorbed and those where they are not present.…”
Section: Introductionmentioning
confidence: 99%